1985
DOI: 10.1007/bf00230905
|View full text |Cite
|
Sign up to set email alerts
|

Cell formation in the motor nucleus and mesencephalic nucleus of the trigeminal nerve of rats made hypothyroid by propylthiouracil

Abstract: Neurogenesis in the motor and mesencephalic nuclei of the trigeminal nerve was examined using autoradiographic techniques. Two groups of pregnant rats (control and experimental) were injected with two successive daily doses of 3H thymidine in an overlapping series starting from day nine of gestation in order to label in their progeny, the dividing precursor of neurons of the motor nucleus and mesencephalic nucleus of the trigeminal nerve. Control group of rats was raised on a standard diet, while the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Thus, as early as day E9, the thyroid status of the fetus has been demonstrated to have important effects on the proliferation and differentiation of neurons in the motor and mesencephalic nuclei of the trigeminal nerve (46). These regions of the central nervous system are formed and undergo maturation early in development, with neuronal proliferation normally complete by day E12 (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as early as day E9, the thyroid status of the fetus has been demonstrated to have important effects on the proliferation and differentiation of neurons in the motor and mesencephalic nuclei of the trigeminal nerve (46). These regions of the central nervous system are formed and undergo maturation early in development, with neuronal proliferation normally complete by day E12 (47).…”
Section: Discussionmentioning
confidence: 99%
“…Disorganization of the cellular layers of the cerebellar cortex has been shown to occur in postnatal hypothyroidism in rats (24). The cellular changes reported by Narayanan and Narayanan (23) are reflected * Progeny of control in behavioral effects. The trigeminal nerve is important for suckling and the PTU-treated pups had difficulty suckling.…”
Section: Data Fom Animalsmentioning
confidence: 94%
“…These neurons normally form relatively early in gestation at a period that would correspond to the first half of gestation in humans (23). Eventually these neurons are produced, but the timing of neuronal birth, migration, and synaptogenesis is finely tuned and if neurons are not formed at the appropriate time, they may never reach the right cell layer of the brain and form normal neuronal synapses.…”
Section: Data Fom Animalsmentioning
confidence: 99%
“…in Zoeller and Rovet, 2004;Bernal, 2005;Bernal, 2007;Williams, 2008). The events controlled by THs comprise cellular proliferation, migration, and neuronal and glial cell differentiation (Narayanan and Narayanan, 1985;Berbel et al, 1993;Berbel et al, 1994;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Clinical and experimental studies have demonstrated that THs are essential for normal brain development.…”
Section: Nervous Systemmentioning
confidence: 99%
“…These deficits depend on specific cellular impairments. Indeed, during the prenatal period, THs influence neurogenesis, neuronal proliferation and migration in the cerebral cortex, hippocampus and medial ganglionic eminence (Narayanan and Narayanan, 1985;Lucio et al, 1997;Auso et al, 2004;Cuevas et al, 2005). Axonal outgrowth, dendritic branching and synaptogenesis, together with the initiation of glial cell differentiation and migration are also affected by TH deficiency at prenatal stages (Portfield and Hendrich, 1993;Morreale de Escobar et al, 2000;Bernal et al, 2003).…”
Section: Nervous Systemmentioning
confidence: 99%